State-of-the-Art Targeted High-Throughput Sequencing for Detecting Inherited Platelet Disorders - Gebetsberger, Jennifer; Mott, Kristina; Bernar, Aline; Klopocki, Eva; Streif, Werner; Schulze, Harald (Hämostaseologie, 2023)
Inherited platelet disorders (IPDs) are a heterogeneous group of rare entities caused by molecular divergence in genes relevant for platelet formation and function. A rational diagnostic approach is necessary to counsel and treat patients with IPDs. With the introduction of high-throughput sequencing at the beginning of this millennium, a more accurate diagnosis of IPDs has become available. We discuss advantages and limitations of genetic testing, technical issues, and ethical aspects. Additionally, we provide information on the clinical significance of different classes of variants and how they are correctly reported.
Keywords: blood platelet disorders; high-throughput nucleotide sequencing; platelets